1979
DOI: 10.1002/pssb.2220960239
|View full text |Cite
|
Sign up to set email alerts
|

Scattering mechanisms of electrons in ZnSe crystals with high mobility

Abstract: I n low-ohmic n-type ZnSe crystals with the room temperature specific resistance of (3 t o 5) rZ cm and electron concentration from 3 x 10l6 to 2 x 10l6Hall-effect, electrical conductivity, and charge carrier mobility is investigated in the temperature interval from 10 t o 300 K. The basic parameters of the samples are determined. It is found from the experimental data that the mobility is higher than the theoretical value in the investigated temperature range. It is argued that in the region of ionized impuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The improvement in the technology of both growing and subsequent heat treatment of n-ZnSe crystals in Zn melt allowed the electron mobility to be increased to (8)(9)) × 10 3 cm 2 /(V s) at 77 K [6,7] and up to the maximum value of 1.2 × 10 4 cm 2 /(V s) at 55 K [6]. The discrepancy between theory and experiment was also observed in the region of scattering by phonons [5], where the experimental values of mobility reached the value of 600 cm 2 /(V s) at 300 K. It was shown [3] that the discrepancy in the region of scattering by impurity ions was due to the inadequacy of known scattering theories based on the Born approximation, since this approximation is valid for ZnSe at T > 100 K, where the scattering by phonons is predominant. A polaron effect was taken into account in [3] in order to co-ordinate the theory with experiment in the region of phonon scattering.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…The improvement in the technology of both growing and subsequent heat treatment of n-ZnSe crystals in Zn melt allowed the electron mobility to be increased to (8)(9)) × 10 3 cm 2 /(V s) at 77 K [6,7] and up to the maximum value of 1.2 × 10 4 cm 2 /(V s) at 55 K [6]. The discrepancy between theory and experiment was also observed in the region of scattering by phonons [5], where the experimental values of mobility reached the value of 600 cm 2 /(V s) at 300 K. It was shown [3] that the discrepancy in the region of scattering by impurity ions was due to the inadequacy of known scattering theories based on the Born approximation, since this approximation is valid for ZnSe at T > 100 K, where the scattering by phonons is predominant. A polaron effect was taken into account in [3] in order to co-ordinate the theory with experiment in the region of phonon scattering.…”
Section: Introductionmentioning
confidence: 58%
“…They have concluded that the acoustic type of scattering is not essential. It was shown later [3] that acoustic-phonon scattering can considerably limit carrier mobility at high temperatures if the value of the deformation potential is equal to 11.5 eV.…”
Section: Introductionmentioning
confidence: 98%
“…The electron mobility in samples annealed in zinc at T b 800 C has a dark value of 520 cm 2 /Vs at room temperature, indicating the high perfection and purity of the original crystal [8]. With temperature decrease, the mobility monotonously increases in conformity with a power law (Fig.…”
mentioning
confidence: 82%
“…Temperature dependence of electron conductivity for the n-ZnSe : Zn samples ( * dark, * illumination). Annealing temperature: (1) 950, (2) 900, (3) 800, (4) 700, (5) 675, (6) 650, (7) 620, (8) 600 C concentration of the V Se which are shallow donors with an ionization energy of % 10 meV. Thus, the observed increase of the concentration of the shallow donor and the decrease of their ionization energy to 9 meV, as the annealing temperature increases, are the consequence of a sharp increase of the V Se native defect concentration.…”
Section: à3mentioning
confidence: 99%
“…On the dielectric side of the M±I transition, as the temperature decreases from room temperature to 100 K, the resistivity falls down and is determined by the scattering of charge carriers by optical phonons with a considerable polaron screening of this process [7]. The increase of the impurity concentration in the samples shifts the minimum in the dependence rT to higher temperatures.…”
mentioning
confidence: 98%